Chinese Alaryngeal Speech Rehabilitation and Their Acoustical Characteristics: A Comprehensive Review - Lawrence Ng Manwa; Mingyue XIONG (康复学报)
As a surgical procedure for late-stage laryngeal cancer, total laryngectomy aims to remove the entire laryngeal structure, including the entire phonatory apparatus. As such, laryngectomized patients suffer the loss of ability to make sound. They have to rely on an alternative phonation method in order to regain speech. Currently, esophageal(SE), tracheoesophageal(TE), electrolaryngeal(EL), and pneumatic artificial laryngeal(PA)speech are available. Different sound characteristics are associated with different alaryngeal speech, mainly due to the use of different phonatory methods. The present paper discusses various alaryngeal phonation and reviews the acoustic, perceptual, and aerodynamic characteristics associated with the four alaryngeal speech, with a special focus on Mandarin and Cantonese Chinese.